1994
DOI: 10.1002/pro.5560031213
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Function analysis of human IL‐6: Identification of two distinct regions that are important for receptor binding

Abstract: Interleukin-6 (IL-6) is a multifunctional cytokine that plays an important role in host defense. It has been predicted that IL-6 may fold as a 4 a-helix bundle structure with up-up-down-down topology. Despite a high degree of sequence similarity (42%) the human and mouse IL-6 polypeptides display distinct species-specific activities. Although human IL-6 (hIL-6) is active in both human and mouse cell assays, mouse IL-6 (mIL-6) is not active on human cells. Previously, we demonstrated that the 5 C-terminal resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 81 publications
(90 reference statements)
4
73
0
1
Order By: Relevance
“…IL-6 has been expressed in rabbit reticulocyte lysate (Geiger et al, 1988), Escherichia coli (Brakenhoff et al, 1987;Tonouchi et al, 1988;Kriittgen et al, 1990a;Yasueda et al, 1990;Arcone et al, 1991a;Grennet et al, 1991;Zhang et al, 1992;Hammacher et al, 1994), Saccharomyces cerevisiae (Guisez et al, 1991), Pichia pastoris (this laboratory, unpublished data), Aspergillus nidulans , Xenopus laevis (Fontaine et al, 1991), baculovirus insect cells and Chinese hamster ovary (CHO) cells (Eisenthal et al, 1993;Orita et al, 1994).…”
Section: Post-translational Modifications Of Recombinant Il-6mentioning
confidence: 99%
See 4 more Smart Citations
“…IL-6 has been expressed in rabbit reticulocyte lysate (Geiger et al, 1988), Escherichia coli (Brakenhoff et al, 1987;Tonouchi et al, 1988;Kriittgen et al, 1990a;Yasueda et al, 1990;Arcone et al, 1991a;Grennet et al, 1991;Zhang et al, 1992;Hammacher et al, 1994), Saccharomyces cerevisiae (Guisez et al, 1991), Pichia pastoris (this laboratory, unpublished data), Aspergillus nidulans , Xenopus laevis (Fontaine et al, 1991), baculovirus insect cells and Chinese hamster ovary (CHO) cells (Eisenthal et al, 1993;Orita et al, 1994).…”
Section: Post-translational Modifications Of Recombinant Il-6mentioning
confidence: 99%
“…These similarities between IL-6 and G-CSF led three groups to use the structure of G-CSF (Hill et al, 1993) as a template to construct three-dimensional models of hIL-6 (Ehlers et al, 1994;Savino et al, 1994b) and mIL-6 (Hammacher et al, 1994). All these models show the expected four-helix bundle topology of the helical cytokines with a small helix in the AB-loop, though the model of Savino et al (1994b) has a second helix in the AB-loop similar to that found in hGH (de Vos et al, 1992).…”
Section: Il-6 and Helical Cytokine Structurementioning
confidence: 99%
See 3 more Smart Citations